Social Philosophy According to Ibn Khaldun: A Study of The Concept of “Human Urbanization” and Its Relationship to Progress (The International Journal for Scientific Research, 2023)
This research deals with Ibn Khaldun’s social philosophy, as contained in his famous introduction, which he wrote as an introduction to his book on history, known as “The Book of Lessons, the Diwan of the Beginner and the News in the Days of the Arabs, Persians, and Berbers, and Those Who Contemporized Them with the Greatest Power.” Due to the multiplicity of topics included in the “Introduction” and their overlap in such a way that it is impossible to separate them, the research was concerned with “human urbanism” in the first place, as it is - according to what the research assumed - the main axis around which Ibn Khaldun’s philosophy revolves, this is through revealing the methodological relationship that links the “science of urbanization” with the science of history, for which Ibn Khaldun stipulated that the historian must understand the phenomena of urbanization and know the causes and reasons that lead to it so that he will be able to distinguish between historical news and its levels of certainty, and separate what is true and real. In it and what is false or delusional.In the context of “urbanization” and its concept, the research shed light on the problem of progress according to Ibn Khaldun, and its connection to the concept of urbanization itself. It reviewed the conditions for achieving progress in human societies based on what can be deduced from the introduction. It is the political, economic, and ideological condition. Then he discussed the main features of progress as a social philosophical problem that was crystallized by Ibn Khaldun's personal interest in politics and society as a scholar and worker in both fields. In addition to its historical coincidence with the eras of decline and decline in Islamic history, which Ibn Khaldun was a witness to in the fourteenth and fifteenth centuries.
Keywords: Ibn Khaldun; civilizational progress; urban science; nervousness; human society; human consciousness; the movement of history